2005
DOI: 10.1212/01.wnl.0000149640.78684.ea
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cognitive dysfunction in patients with systemic lupus erythematosus

Abstract: Regular aspirin use is associated with improved cognitive function in older patients with systemic lupus erythematosus (SLE) in conjunction with the presence of other vascular risk factors. Regular prednisone use is associated with decreased cognitive functioning in middle-aged patients with SLE. Although this prednisone effect was independent of measures of SLE-associated disease activity, the authors cannot exclude the possibility that consistent prednisone use is a surrogate for more severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
113
3
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(125 citation statements)
references
References 36 publications
3
113
3
6
Order By: Relevance
“…A pivotal role of aPL in NPSLE and their predictive value for NP damage progression are well known [22][23][24][25][26][27][28][29][30][31][32] and substantially confirmed also by the present study. Other factors deemed as related to NP involvement have been previously proposed including high disease activity, caucasian ethnicity, presence of anti-Ro/SSA antibodies [20,21], vasculitis, nephritis, anti-dsDNA, LA and anti-Sm [23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A pivotal role of aPL in NPSLE and their predictive value for NP damage progression are well known [22][23][24][25][26][27][28][29][30][31][32] and substantially confirmed also by the present study. Other factors deemed as related to NP involvement have been previously proposed including high disease activity, caucasian ethnicity, presence of anti-Ro/SSA antibodies [20,21], vasculitis, nephritis, anti-dsDNA, LA and anti-Sm [23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 86%
“…Other factors deemed as related to NP involvement have been previously proposed including high disease activity, caucasian ethnicity, presence of anti-Ro/SSA antibodies [20,21], vasculitis, nephritis, anti-dsDNA, LA and anti-Sm [23][24][25][26][27][28]. In particular, aPL and use of GC, diabetes, depression, low levels of education have been related with cognitive dysfunction [30], which improved after prolonged use of aspirin, thus supporting the hypothesis of an impaired vascular supply in the pathogenesis of this complication. Other authors, also, found a correlation between cognitive dysfunctions and the presence of aPL, hypertension, Raynaud's phenomenon, disease-related cumulative damage [31,33].…”
Section: Discussionmentioning
confidence: 99%
“…153 Anti-platelet and anti-coagulation therapy is still controversial, with regard to theoretical vascular and thrombotic pathogenesis in the absence of anti-phospholipid antibodies, with only one longitudinal observational study showing that regular aspirin use in adult SLE was not associated with better cognitive performance compared to those who were not. 154 Again no such study exists in childhood-onset SLE.…”
Section: Pharmacological Therapiesmentioning
confidence: 99%
“…Не-редко имеется несколько факторов риска, при этом происхо-дит усиление их неблагоприятного воздействия. При 3-лет-нем наблюдении за 123 пациентами выявлялись такие сосуди-стые факторы риска, как гиперхолестеринемия (17,1%), СД (21,1%) и АГ (48,0%), а ухудшение когнитивных функций ас-социировалось с повышением уровня АФЛ (54%), длитель-ным приемом преднизолона, наличием СД, высоким уровнем депрессии и низким уровнем образования [13,14].…”
unclassified